In silico product design of pharmaceuticals - Johan Boetker; Dhara Raijada; Johanna Aho; Milad Khorasani; Søren V. Søgaard; Lærke Arnfast; Adam Bohr; Magnus Edinger; Jorrit J. Water; Jukka Rantanen (Elsevier, 2016)
The increasing demand for personalized medicine necessitates the production of easily customizable dosage forms. As the number of possible dosage forms may scale toward infinity, their uniqueness requires a versatile production platform and numerical simulation in order to be manufactured efficiently. A mathematical description of these systems is the only feasible approach to manage such diverse properties of different products. However, experimental verification is still essential for evaluation of processability and related concomitant phenomena, such as possible solid state changes that may occur during production and storage.